Mapping the Active Galactic Nucleus Effects on the Stellar and Gas Properties of NGC 5806 - Sophie L. Robbins; Sandra I. Raimundo; Matthew A. Malkan (The Astrophysical Journal)
It is commonly accepted that active galactic nuclei (AGNs) have a strong impact upon the evolution of their host galaxies, but the processes by which they do so are not fully understood. We aim to further the understanding of AGN feeding and feedback by examining an active galaxy using spatially resolved spectroscopy. We analyze integral field spectroscopy of the active galaxy NGC 5806, obtained using the Very Large Telescope Multi-Unit Spectroscopic Explorer. We map the dynamics of gas and stars, as well as gas optical emission line fluxes throughout the central 8 × 8 kpc ^2 of the galaxy. We use emission line ratios to map gas metallicity and identify regions of gas excitation dominated by AGN/shocks or star formation. We also determine the average stellar population age and metallicity, and model the rotation and dynamics of the galaxy. We find that NGC 5806 has a star-forming circumnuclear ring, with a projected radius of ~400 pc. The dynamics of this galaxy are driven by a large-scale bar, which transports gas from the spiral arm to the central ring and potentially fuels the AGN. We also observe AGN-dominated gas excitation up to 3.3 kpc away from the center of the galaxy, showing the extended AGN effect on the gas in the central regions of the galaxy.